Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Define $f:\mathbb{Z}\to\mathbb{N}$ by $f(n)=3n^2 + 2n + 5$. Prove that $f:\mathbb{Z}\to\mathbb{N}$ and that $f$ is one-to-one.

I have the definitions of a function and one-to-one, but I'm just new to this sort of material. I would appreciate if someone could walk me through how to at least start this problem.

Thanks.

share|improve this question
    
Hint: $3n^2 + 2n + 5 = 2n^2 + 4 + (n+1)^2$. Is this always positive? Is it increasing? –  M.B. Oct 17 '12 at 18:58

3 Answers 3

up vote 3 down vote accepted

You have to prove two things. In order to show that $f:\Bbb Z\to\Bbb N$, you must show that $f(n)\in\Bbb N$ for every $n\in\Bbb Z$. In other words, you must show that for each integer $n$, the number $3n^2+2n+5$ is in $\Bbb N$. It’s clear that $f(n)$ is always an integer: it’s a sum of products of integers. What may not be immediately obvious is that it’s always non-negative and therefore in $\Bbb N$ rather than just in $\Bbb Z$. One easy way to see this is to complete the square:

$$\begin{align*} f(n)&=3n^2+2n+5\\ &=3\left(n^2+\frac23n+\frac53\right)\\ &=3\left(\left(n+\frac13\right)^2-\frac19+\frac53\right)\\ &=3\left(n+\frac13\right)^2+\frac{14}3\\ &\ge\frac{14}3\;, \end{align*}$$

since $\left(n+\frac13\right)^2$ is always at least $0$.

The other thing that you must prove is that $f$ is one-to-one. There’s a standard approach to this that works nicely in most simple problems: assume that $f(n)=f(m)$ for some integers $m$ and $n$, and prove that this forces $m=n$. That shows that if you start with $m\ne n$, you can never get $f(m)=f(n)$, and hence that $f$ is one-to-one.

So begin by supposing that $n,m\in\Bbb Z$ and $f(n)=f(m)$. This simply means that $$3n^2+2n+5=3m^2+2m+5\;,\tag{1}$$ and all that you have to do is manipulate $(1)$ algebraically until you can infer that $n=m$. Here’s a hint to get you started: $(1)$ is equivalent to $$3\left(n^2-m^2\right)+2(n-m)=0\;,$$ and if you factor the lefthand side, this becomes $$(n-m)\Big(3(n+m)+2\Big)=0\;.$$ If a product of two numbers is $0$, what can you say about the numbers? What does that tell you here about $n$ and $m$?

share|improve this answer

We need to show that if $f(m)=f(n)$ then $m=n$. So suppose that $3m^2+2m+5=3n^2+2n+5$. Then $$3(m^2-n^2)=-2(m-n).$$ Note that $m^2-n^2=(m-n)(m+n)$. So if $m\ne n$, then by cancellation we get $$3(m+n)=-2.$$ This is not possible, since $3$ divides the left-hand side but $3$ does not divide $-2$.

We also need to show that $f(n)$ is positive for all integers $n$. The no-thinking way of doing this is to complete the square. If we want to think a little more and compute less, we can note that $3n^2+2n+5\ge n^2+2n+5=(n+1)^2+4$.

share|improve this answer
    
Nicely done. Your factoring and cancelling gets the 1-1 immediately. And I also agree it's not necessary to show the square-completion part of the argument, presumably the problem poser should be able to do that. –  coffeemath Oct 17 '12 at 19:10

Clearly $f(n)\in\mathbb Z$ for all $n\in \mathbb Z$. Moreover, $3n^2+2n+5 = \frac13\left(3n+1\right)^2+\frac{14}3\ge \frac{14}3\ge1$. From $f(n)\in\mathbb Z$ and $f(n)\ge 1$, we conclude $f(n)\in \mathbb N$, so $f$ is indeed a function $\mathbb Z\to\mathbb N$.

For one-ton-one, assume $f(n)=f(m)$. Then $\frac13\left(3n+1\right)^2+\frac{14}3=\frac13\left(3m+1\right)^2+\frac{14}3$, hence $(3n+1)^2=(3m+1)^2$, i.e. $0=(3n+1)^2-(3m+1)^2=(3n+3m+2)(2n-2m)$. The first factor is one less than a multiple of $3$, hence nonzero. Hence $m=n$. We have shown that $f(n)=f(m)$ implies $n=m$, i.e. $f$ is one-to-one.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.